The effect of HarpinEa protein on promoting growth in wheat and inducing resistance to root rot disease (Damascus University Journal of agriculture sciences, 2025)
This study conducted to evaluate the effect of Harpin protein, produced at Atomic Energy Commission-Syria, on the growth of wheat. The percent of germination, root and peduncle length, number of roots, wet and dry seedling weight, and chlorophyll concentration were recorded as primary indicators of growth; The experiment showed that there was a significant effect of Harpin on length of  root and peduncle and in wheat seedlings compared to control. also, there  was asignificant increase in wet and dry weight of seedlings treated with Harpin., the amount of chlorophyll increased significantly from 11.2 mg/100 g in  control to 14.2 mg/100 g in the seedlings treated with Harpin.On the other hand, we study the effect of Harpin protein on wheat resistance to root rot disease. We used three fungal isolates of Fusarium, Pethium, Rhizictonia in this study,  the results showed that harbin protein  stimulated response defense in wheat against root rots, compared to the control.As a result, we find that the harbin protein- produced locally- showed good preliminary results in promoting growth in wheat and inducing resistance to root rot disease, therefore it is recommended to use it and conduct other studies on other plants and diseases in future.
Keywords: Harpin; Wheat; Promoting Growth And Inducing Resistance; Roots Rots